2015
DOI: 10.1097/md.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Nonpenetrating Deep Sclerectomy For Glaucoma After Descemet Stripping Automated Endothelial Keratoplasty

Abstract: The purpose of this study was to evaluate the efficacy and safety of nonpenetrating deep sclerectomy (NPDS) in 3 consecutive eyes with preexisting and uncontrolled glaucoma after Descemet stripping with automated endothelial keratoplasty (DSAEK).NPDS with intrascleral implant and topical adjunctive intraoperative mitomycin C (0.2 mg/mL 1 minute) was performed.Intraocular pressure (IOP) and number of glaucoma medication were registered before and after NPDS with at least 1-year follow-up. Intraoperative and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…NPDS was as effective as trabeculectomy in controlling intraocular pressure, but its long-term survival rate of the graft after surgery was better ( 53 ). Another study using NPDS after DSAEK for glaucoma came to the same conclusion ( 55 ).…”
Section: Treatment Of Secondary Glaucoma After Keratoplastymentioning
confidence: 60%
“…NPDS was as effective as trabeculectomy in controlling intraocular pressure, but its long-term survival rate of the graft after surgery was better ( 53 ). Another study using NPDS after DSAEK for glaucoma came to the same conclusion ( 55 ).…”
Section: Treatment Of Secondary Glaucoma After Keratoplastymentioning
confidence: 60%
“…The authors reported that the main advantage of NPDS over trabeculectomy was the unnecessary intraoperative entry in the AC. 5 The implant of glaucoma drainage devices (GDDs) has been investigated only in post-PK eyes, for those cases a good IOP control was reported. 11,12 On one hand, GDDs reduce the risk of hypotony and AC collapse in the early post-operative period; on the other hand, a higher rate of graft failure, when comparing GDD to trabeculectomy, was registered: in particular, a 50% probability of graft failure has been reported at 2 years following Ahmed valve implantation.…”
Section: Np196mentioning
confidence: 99%
“…2 Trabeculectomies, non-penetrating deep sclerectomies, glaucoma drainage devices, and cyclodestructive procedures have been reported in cases of glaucoma surgery following DSAEK. 2,4,5 Except from the specific cases of a post-traumatic eye with chronic intraocular inflammation 6 and a patient with ICE syndrome, 7 no cases of Xen45 Gel Stent implantation (Allergan, Dublin, Ireland) have been previously published in a primary open angle glaucoma after DSAEK.…”
Section: Introductionmentioning
confidence: 99%